2004
DOI: 10.1007/s00248-004-0001-2
|View full text |Cite
|
Sign up to set email alerts
|

A Shallow BTEX and MTBE Contaminated Aquifer Supports a Diverse Microbial Community

Abstract: Microbial communities in subsurface environments are poorly characterized and the impacts of anthropogenic contamination on their structure and function have not been adequately addressed. The release of contaminant(s) to a previously unexposed environment is often hypothesized to decrease the diversity of the affected community. We characterized the structure of microbial communities along a gradient of benzene, toluene, ethylbenzene, and xylene (BTEX) and methyl-tert-butyl-ether (MTBE) contamination, resulti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(26 citation statements)
references
References 61 publications
2
24
0
Order By: Relevance
“…It was observed that the majority of the microorganisms belonged to the a-, band c-Proteobacteria classes, which contain several oil-degrading bacteria (Hristova et al 2001;Feris et al 2004). The most frequently detected class was b-Proteobacteria, to which most currently known MTBE-degraders belong (Bruns et al 2001;Hatzinger et al 2001).…”
Section: Composition Of the Microbial Consortiamentioning
confidence: 97%
“…It was observed that the majority of the microorganisms belonged to the a-, band c-Proteobacteria classes, which contain several oil-degrading bacteria (Hristova et al 2001;Feris et al 2004). The most frequently detected class was b-Proteobacteria, to which most currently known MTBE-degraders belong (Bruns et al 2001;Hatzinger et al 2001).…”
Section: Composition Of the Microbial Consortiamentioning
confidence: 97%
“…However, the introduction of labile carbon into carbon-limited subsurface environments (e.g., before or long after spills of gasoline) or electron donors (e.g., as in the case of many MTBE plumes) can dramatically change prevailing redox conditions and can alter the structure and function of subsurface microbial communities. 1,2 Functional changes may include preferential degradation of more labile carbon substrates over other biodegradable and more toxic compounds present (e.g., benzene (B), toluene (T), xylene (X), and ethylbenzene (E)). 3 A growing body of work has examined the influence of ethanol on the natural attenuation and biodegradation of BTEX under both aerobic and anaerobic conditions [4][5][6][7][8] These studies suggest that simultaneous introduction of ethanol and BTEX will result in decreased BTEX attenuation rates and longer contaminant plumes.…”
Section: Introductionmentioning
confidence: 99%
“…Recent genome sequencing projects targeting bacteria belonging to this group promoted insights into their lifestyle and revealed them to be best suited to low-nutrient conditions (37)(38)(39). Holophaga foetida TMBS4T was even capable of degrading several aromatic compounds, such as gallate, phloroglucinol, and pyrogallol, under anaerobic conditions (37,40), and members of the Acidobacteria have also been identified as abundant in a gasoline spill (41) and even discussed as benzene degraders (15). How far Acidobacteria may be involved in the degradation of pollutants under analysis here remains to be elucidated.…”
Section: Resultsmentioning
confidence: 99%